Understanding the Prooxidant Action of Plant Polyphenols in the Cellular Microenvironment of Malignant Cells: Role of Copper and Therapeutic Implications - Farhan, Mohd; Rizvi, Asim (Frontiers in Pharmacology, 2022)
Plant derived polyphenolic compounds are considered critical components of human nutrition and have shown chemotherapeutic effects against a number of malignancies. Several studies have confirmed the ability of polyphenols to induce apoptosis and regression of tumours in animal models. However, the mechanism through which polyphenols modulate their malignant cell selective anticancer effects has not been clearly established. While it is believed that the antioxidant properties of these molecules may contribute to lowering the risk of cancer induction by causing oxidative damage to DNA, it could not be responsible for chemotherapeutic properties and apoptosis induction. It is a well known fact that cellular copper increases within the malignant cell and in serum of patients harbouring malignancies. This phenomenon is independent of the cellular origin of malignancies. Based on our own observations and those of others; over the last thirty years our laboratory has shown that cellular copper reacts with plant derived polyphenolic compounds, by a Fenton like reaction, which generates reactive oxygen species and leads to genomic DNA damage. This damage then causes an apoptosis like cell death of malignant cells, while sparing normal cells. This communication reviews our work in this area and lays the basis for understanding how plant derived polyphenols can behave as prooxidants (and not antioxidants) within the microenvironment of a malignancy (elevated copper levels) and gives rationale for their preferential cytotoxicity towards malignant cells.